2018
DOI: 10.3389/fphys.2018.00848
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Blood Pressure Response to a High-Salt Diet in Mice With Reduced Global Expression of the Glucocorticoid Receptor

Abstract: Salt-sensitive hypertension is common in glucocorticoid excess. Glucocorticoid resistance also presents with hypercortisolemia and hypertension but the relationship between salt intake and blood pressure (BP) is not well defined. GRβgeo/+ mice have global glucocorticoid receptor (GR) haploinsufficiency and increased BP. Here we examined the effect of high salt diet on BP, salt excretion and renal blood flow in GRβgeo/+mice. Basal BP was ∼10 mmHg higher in male GRβgeo/+ mice than in GR+/+ littermates. This mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…We confirmed the diurnal rhythm of pNCC (19,49), further finding that chronic systemic GR antagonism perturbed this rhythm. This prompted assessment of diurnal variation in pNCC in mice with a genetically induced reduction in GR expression (18,27). We were only able to assess pNCC in GR heterozygote null mice at two time points using archived kidney protein homogenates, the midpoints of the subjective day and night, but our data indicate that reduced GR expression significantly dampened the pNCC phosphorylation rhythm.…”
Section: Discussionmentioning
confidence: 90%
“…We confirmed the diurnal rhythm of pNCC (19,49), further finding that chronic systemic GR antagonism perturbed this rhythm. This prompted assessment of diurnal variation in pNCC in mice with a genetically induced reduction in GR expression (18,27). We were only able to assess pNCC in GR heterozygote null mice at two time points using archived kidney protein homogenates, the midpoints of the subjective day and night, but our data indicate that reduced GR expression significantly dampened the pNCC phosphorylation rhythm.…”
Section: Discussionmentioning
confidence: 90%
“…Previous in vitro and in vivo studies proposed a role of GR in renal MR-mediated Na + transport in a compensatory and/or cooperative manner (Berger et al, 1998; Gaeggeler et al, 2005; Hunter et al, 2014; Canonica et al, 2016; Terker et al, 2016; Ivy et al, 2018), although it could not yet be functionally confirmed. In this study, we used adult inducible nephron-specific GR knockout ( Nr3c1 Pax8/LC1 ) mice to explore the consequences of renal tubular GR deletion for Na + handling and blood pressure regulation.…”
Section: Discussionmentioning
confidence: 94%
“…Ivy and coworkers recently reported that mice with global GR haploinsufficiency exhibit increased blood pressure that is further increased by high salt diet. In this model, corticosterone, and to a lesser extent deoxycorticosterone excretion, was increased in mutant mice following a high-salt challenge, that may lead to systemic effects (Ivy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not enough to counteract GR actions to increase blood pressure. Perhaps, this response also includes the action of mineralocorticoids as seen in mice with GR haploinsufficiency (Ivy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%